Rebuilding the Unseen: From the Wounds of Conflict to Reconstructing Libyan Society A Social Work Perspective - Dr. Najat Al-Hadi Abdullah Mohammed (Journal of Scientific and Human Dimensions, 2026)
For decades, Libya has been affected by invisible social wounds caused by recurring conflicts, profoundly impacting interpersonal trust, family and community bonds, and traditional social values and practices. This study aims to analyze these wounds and explore strategies for reconstructing Libyan society from a social work perspective, focusing on restoring social cohesion and empowering local communities. Findings indicate that Libyan society remains fragile and requires systematic professional interventions, including community empowerment, psychosocial rehabilitation programs, and enhancing social cohesion, while integrating traditional initiatives with professional social work expertise ,The study offers practical recommendations, including developing social workers’ capacities, promoting community participation, reviving traditional social values, and coordinating between official institutions and civil society to ensure sustainable outcomes.